High Rate Stormwater Treatment for Water Reuse and Conservation—Review - Saravanamuthu Vigneswaran; Jaya Kandasamy; Harsha Ratnaweera (Applied Sciences)
Effective stormwater management is increasingly vital due to climate change impacts, such as intensified rainfall and flooding. Urban expansion, water scarcity, and intensified agriculture demand innovative solutions like Green Stormwater Infrastructure (GSI), including vegetated biofilters, green roofs, wetlands, bioretention systems, and high-rate filtration. These systems, enhanced by natural and engineered filter materials, improve contaminant removal across diverse contexts. Modern practices prioritize retention, infiltration, and groundwater recharge over traditional rapid drainage, reframing stormwater as a resource amid rising extreme weather events. In water-scarce regions, stormwater management offers dual-use potential for drinking and non-drinking applications, addressing freshwater scarcity exacerbated by population growth and climate change. Targeting the “first flush” of pollutants after rainfall allows for more efficient, cost-effective treatment. This paper identifies three key objectives: addressing GSI limitations and exploring new technologies, evaluating treatment train combinations for cost-effective reuse, and advancing urban stormwater treatment research. Various filter media, such as those in green roofs, bioretention systems, and swales, effectively remove pollutants like nutrients, heavy metals, PAHs, and micropollutants. Granular activated carbon (GAC) filters excel at reducing heavy metals and dissolved organic carbon (DOC), with pre-screening via anthracite filters to extend GAC lifespan by trapping sediments and pollutants. Managing emerging contaminants and microplastics remains underexplored and requires further investigation.